The effect of turbulence intensity on local skin temperature and subjective responses to draft - Wang, Yuemei; Lian, Zhiwei; Lan, Li (Energy and buildings, 2011)
• We studied the relationship between turbulence intensity, local skin temperature drop before and after exposure on the back of the neck, and subjects’ response to draft. • We found that local skin temperature drop is larger under higher turbulence intensity than that under lower turbulence intensity. • Percentage of subjects dissatisfied to draft was correlated to the local skin temperature. • Local skin temperature can be considered to be an indicator to build the model predicting draft under non-uniform environments. The aim of the present study was to investigate whether turbulence intensity affects local skin temperature drop, and whether subjects’ dissatisfaction with draft can be correlated to the local skin temperature drop. Eighteen subjects were exposed to two levels of turbulence intensity (15% and 30%) at mean air velocities of 0.3 and 0.6m/s respectively for 1h. Subjective responses to draft were registered every 10min and skin temperatures at the back of the neck were recorded throughout the sessions. More subjects felt uncomfortable due to draft when exposed to high turbulence than exposed to low turbulence. Skin temperature drop after 1h exposure under high turbulence intensity is significantly larger than that under low turbulence intensity. Percentage of subjects dissatisfied with draft positively correlated to the local skin temperature drop.